KAJIAN SPASIAL KONDISI TERUMBU KARANG DAN PADANG LAMUN DI PULAU KETAWAI KABUPATEN BANGKA TENGAH - WAHYU ADI; SUDIRMAN ADIBRATA; FRANT0 FRANT0 (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2013)
Coastal ecosystem that usually found are coral reefs and sea grass beds. Coral reefs and sea grass beds data in spatial should be known, to determine management measure for an area. The research is conducted by interpretation of Aster Image Satellite and collected coral reefs and sea grass beds data. The research conclusion is distribution of coral reefs and sea grass beds (in spatial map), with sea grass condition as mediocre (not healthy), damaged coral reefs at west of Ketawai Island